Long Non-coding RNAs as Local Regulators of Pancreatic Islet Transcription Factor Genes - Font-Cunill, Berta; Arnes, Luis; Ferrer, Jorge; Sussel, Lori; Beucher, Anthony (Frontiers in Genetics, 2018)
The transcriptional programs of differentiated cells are tightly regulated by interactions between cell-type specific transcription factors and cis-regulatory elements. Long non-coding RNAs (lncRNAs) have emerged as additional regulators of gene transcription. Current evidence indicates that lncRNAs are a very heterogeneous group of molecules. For example, selected lncRNAs have been shown to regulate gene expression in cis or trans, although in most cases the precise underlying molecular mechanisms is unknown. Recent studies have uncovered a large number of lncRNAs that are selectively expressed in pancreatic islet cells, some of which were shown to regulate beta cell transcriptional programs. A subset of such islet lncRNAs appears to control the expression of beta cell-specific transcription factor genes by local cis-regulation. In this review, we discuss current knowledge of molecular mechanisms underlying cis-regulatory lncRNAs and discuss challenges involved in using genetic perturbations to define their function. We then discuss known examples of pancreatic islet lncRNAs that appear to exert cis-regulation of transcription factor genes. We propose that cis-regulatory lncRNAs could represent a molecular target for modulation of diabetes-relevant genes.